2019
DOI: 10.1016/j.neuroimage.2019.116063
|View full text |Cite
|
Sign up to set email alerts
|

No language unification without neural feedback: How awareness affects sentence processing

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 73 publications
1
9
0
Order By: Relevance
“…Taken together, reports of subliminal multi‐word integration have been largely refuted. In contrast with earlier studies, replication attempts or studies with more rigorous methodologies (Mongelli et al, 2019; Rabagliati et al, 2018; Yang et al, 2017) have all found null results. Remarkable claims reported more recently (Hung & Hsieh, 2021; Tu, Liu, et al, 2019; Tu, Wan, et al, 2019) awaits further assessment.…”
Section: Current Reports Of Subliminal Integrationmentioning
confidence: 67%
See 2 more Smart Citations
“…Taken together, reports of subliminal multi‐word integration have been largely refuted. In contrast with earlier studies, replication attempts or studies with more rigorous methodologies (Mongelli et al, 2019; Rabagliati et al, 2018; Yang et al, 2017) have all found null results. Remarkable claims reported more recently (Hung & Hsieh, 2021; Tu, Liu, et al, 2019; Tu, Wan, et al, 2019) awaits further assessment.…”
Section: Current Reports Of Subliminal Integrationmentioning
confidence: 67%
“…Specifically, among all studies that found no SI effect despite above‐chance awareness (i.e. ‘Above‐chance: Yes’ in Figure 2), those that also included a visible condition all managed to find significant results there (Correa et al, 2018; Faivre et al, 2019; Heycke et al, 2017; Heycke & Stahl, 2020; Mongelli et al, 2019; Stahl et al, 2016), with Zher‐Wen and Yu (2021) also finding significant results only in the ‘reduced‐visibility’ (but not the subliminal) groups (see the Discussions section). These suggest that the lack of SI effects was not due to the tasks lacking sensitivity, as significant effects were found in the visible conditions.…”
Section: Current Reports Of Subliminal Integrationmentioning
confidence: 98%
See 1 more Smart Citation
“…This model represents a counterpoint to the conviction that we have elaborate and sophisticated unconscious thinking (Chater, 2018), for which words are only a reflection. Indeed, though it seems incontestable that there is unconscious processing, there is little robust evidence for complex unconscious processing in arithmetic Hesselmann, 2019, 2018;Shanks, 2017), decision making (Acker, 2008;Newell and Shanks, 2014;Nieuwenstein et al, 2015;Vadillo et al, 2015), working memory (Taglialatela Scafati, 2019;Trübutschek et al, 2019), or sentence understanding (Cohen et al, 2021;Mongelli et al, 2019;Nakamura et al, 2018;Rabagliati et al, 2018;Tu et al, 2020;Yang et al, 2017).…”
Section: Mental Healthmentioning
confidence: 99%
“…For non-pathological forms of consciousness and memory it is essential that the conscious sequence is organized in a certain order [45]. For example, comprehension of a sentence is determined by the ability to remember its beginning through its duration and to reach its end producing a coherent discourse [46]. Now, if instantaneous unity is part of the definition of consciousness, then unity organized through time (duration) is essential to consciousness, even if it is not necessary for the existence of conscious subjectivity.…”
Section: Unitas Multiplexmentioning
confidence: 99%